The uremic toxin p-cresol promotes the invasion and migration on carcinoma cells via Ras and mTOR signaling. (August 2019) - Hsu, Yueh-Han; Huang, Hui-Pei; Chang, Horng-Rong
Abstract: P-cresol (PC) shows toxic effects on a variety of cells such as renal proximal tubular cells, glomerular mesangial cells, vascular smooth muscle cells, vascular endothelial cells, cardiomyocytes, cardiac fibroblasts, monocytes, osteoblasts and osteoclasts. The molecular mechanism and role of PC in the progression of urothelial carcinoma have not been documented. To understand the impact of PC on bladder cancer progression, human bladder cancer TSGH8301 cells were treated PC with various concentration (25-100 μM). MTT assay revealed the toxicity of PC on TSGH8301 cells dose-dependently. MMP-2 and MMP-9 expressions of the PC-treated cells were enhanced by using gelatin zymography. The wound healing assay and transwell migration analysis were performed to assay the migratory and invasive effects of PC on TSGH8301 cell and the migrated cell numbers were markedly increased by PC treatment. Moreover, we further detected the expression of Ras, PI3K and Akt proteins that involved in the invasion/migration of the cancer. Inhibiting the Ras and mTOR signaling pathways by Y27632 or/and everolimus improved cancer cell progression induced by PC. This study may clarify the impact of PC on migration and invasion of carcinoma cells. Highlights: The uremic toxin, p-cresol is related to TSGH8301 cancer cells progression. p-cresol activates proliferation and migration of the cancer cells. Above mechanisms involve the Ras and mTOR signaling pathways. Combination of Ras and mTOR inhibitors suppress the migration/proliferation.